Reconfigurable Magneto-Electric Dipole Antennas for Base Stations in Modern Wireless Communication Systems. (15th May 2018) - Ge, Lei; Yang, Xujun; Dong, Zheng; Zhang, Dengguo; Zeng, Xierong
Abstract : Magneto-electric (ME) dipole antennas, with the function of changing the antenna characteristics, such as frequency, polarization, or radiation patterns, are reviewed in this paper. The reconfigurability is achieved by electrically altering the states of diodes or varactors to change the surface currents distributions or reflector size of the antenna. The purpose of the designs is to obtain agile antenna characteristics together with good directive radiation performances, such as low cross-polarization level, high front-to-back ratio, and stable gain. By reconfiguring the antenna capability to support more than one wireless frequency standard, switchable polarizations, or cover tunable areas, the reconfigurable ME dipole antennas are able to switch functionality as the mission changes. Therefore, it can help increase the communication efficiency and reduce the construction cost. This shows very attractive features in base station antennas of modern wireless communication applications.